Pengembangan Media E-Booklet Keragaman Spesies Jamur Makroskopis dan Peranannya di Kebun Kelapa Sawit Desa Teluk Merbau untuk Pembelajaran Biologi SMA - Uvi Laila; Wan Syafi’i; Fitra Suzanti (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop an e-booklet media from the results of the study of the diversity of macroscopic fungal species and their roles in the Teluk Merbau Village Oil Palm Plantation for high school biology learning. This type of research is a qualitative descriptive study. The determination of the observation location used the purposive sampling method, namely making 6 line transect lines in locations that represent the age of oil palm trees and fungal habitats. The e-booklet development method uses the ADDIE model until the third step (Development). The developed e-booklet was validated by 2 expert lecturers. The results of the study showed that there were 22 species of macroscopic fungi in the Teluk Merbau Village Oil Palm Plantation area consisting of 21 species from the basidiomycota division and 1 species from the ascomycota division. The results of the validation of the development of the e-booklet on the diversity of macroscopic fungal species and their roles in the Teluk Merbau Village Oil Palm Plantation based on aspects of content, language and appearance obtained an average score of 3.89 which is included in the very valid category, this indicates that the developed e-booklet is in accordance with the criteria for good learning media.